Pengaruh Likuiditas, Perencanaan Pajak dan Penghindaran Pajak terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Perkebunan Bursa Efek Indonesia - Emi Novi Yanti; Ninin Non Ayu Salmah; Aprizal Rosadian (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study investigates the influence of liquidity, tax planning, and tax avoidance on firm value in plantation sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2021-2023. The research addresses the gap in prior studies, which largely focused on manufacturing and banking sectors, while limited evidence exists for the plantation industry that is highly affected by external factors such as commodity prices and production cycles. A quantitative method with a purposive sampling approach was applied, using secondary data obtained from the IDX official website. Regression analysis was conducted after classical assumption tests to ensure model validity. The findings reveal that liquidity has no significant effect on firm value, indicating that short-term solvency is less prioritized by investors in this sector. In contrast, tax planning and tax avoidance positively and significantly affect firm value, reflecting investor appreciation of effective tax management that enhances profitability and shareholder wealth. Furthermore, the simultaneous test confirms that liquidity, tax planning, and tax avoidance collectively contribute significantly to firm value. This study provides both theoretical implications for agency theory and practical insights for managers and investors to optimize tax strategies while maintaining firm value growth.